Fiscal consolidation in developed and emerging economies - Camuri, Paulo André; Jayme Jr., Frederico G.; Hermeto, Ana Maria (Nova Economia, 2016)
The debate regarding fiscal policy has given support to the formulation of an economic policy based on control of indebtedness and in persecution of public savings, acting as important support for the economic growth. This paper presents evidence that counter acts this theory of expansionary austerity. A set of panel data regressions is estimated – through Driscoll & Kraay’s, FGLS, panel corrected standard errors, and SUR estimators and the causality test approach proposed by Kónya (2006) – in search of robust inference related to the main determinants that encompasses the fiscal framework. Our conclusion is that the empirical evidence - using a set of 20 developed economies and other of 24 emerging economies - suggests that identical economic policies for different countries might conduce to results that are opposite to the desired outcome. Notwithstanding the adverse effects associated to explosive debt path, the search for “fiscal space” should be determined essentially by a pro-growth agenda. This is particularly important for the emerging economies facing the transition path challenges.